Les humanités numériques, un révélateur de l’écart épistémologique entre l’histoire et l’économie - Laurent Gauthier (Humanités Numériques)
Why is the use of digital humanities so uncommon in economics, and more specifically in cliometrics – the branch of economics concerned with history – while it is very common in history? To answer this question, we begin by analysing the epistemological distinctions between history and economics, as well as those between economic history and cliometrics. On this basis, and because of these epistemological differences, we then show that the use of digital humanities has been constructed in divergent manners in history and economics.